PENGEMBANGAN LKS BERBASIS INKUIRI TERBIMBING UNTUK MEMBERDAYAKAN LITERASI LINGKUNGAN SISWA KELAS V SDN 5 BABADAN KECAMATAN NGAJUM - Kusumaningrum, Diana; Tanti, Yuli Ika (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
This study aims to: (1) find out the level of validity of guided inquiry-based worksheets to empower students' environmental literacy, (2) to know the readability of guided inquiry-based worksheets to empower students' environmental literacy, (3) find out guided inquiry-based worksheets can empower environmental literacy skills in guided inquiry-based worksheets to empower students' environmental literacy. This is a Research and Development (R&D) research. The model used is the Borg & Gall model. The subjects of the study were fifth grade students of SDN Babadan 5, Ngajum Subdistrict, Malang Regency in 2019/2020 learning year, which consisted of 20 students. In this study the main material used is on the water cycle science subjects. The instruments used included test questions, lesson plans, teacher and student action questionnaires, student responses, RPP validations, worksheet validations, test question validations, and assessment of motor activities on students. The data generated in the form of validation of LKS products, test questions, and lesson plans, the results of the pretest and posttest, student responses, self-assessment and peer assessment, and assessment of student motor activities. Based on the results of the study show that: (1) the quality of the guided inquiry-based worksheets to empower students' environmental literacy can be viewed from the overall feasibility aspects both good and very suitable for use in learning, (2) the practicality of worksheets can be seen from the questionnaire responses of students who get the number a score of 376 with an average of 18.8 with a percentage of 94% categorized as "very good" in the use of teaching materials LKS, (3) the category of environmental literacy skills assessment in the development of this worksheet also showed very good results seen from the results of self assessment assessment that has been done by researchers shows a percentage of 93%, while peer assessment shows a percentage of 92% with a very good category